Analysis of the Influence of the External Environment on KFC - Iveren Monica; Shechah Majesty; Devlin Wang; Chrisderry Chrisderry; Jeremy Kent (Jurnal Ilmu Manajemen Profitability, 2024)
In running a company, there are many factors that influence the performance and performance of the company. These factors can come from inside or outside the company. Therefore, analyzing these factors is a very important step in planning the strategy that the company will use. The discussion in this article focuses more on external analysis or what is usually called External Environment Analysis. The company that will be discussed in this article is Kentucky Fried Chicken (KFC). This research aims to determine the influence of the external environment on the company and identify the competition the company faces. This research uses a quantitative analysis method for the PESTEL factors of the KFC company. The results of the analysis include political, economic, social, technological, environmental and legal factors that can influence the KFC company. Apart from that, there is also a five forces of competition model used by the KFC company. After analyzing the KFC company, there are suggestions that can help KFC in running business in the future.